115 COMPARATIVE ANALYSIS OF HIGHER EDUCATION MANAGEMENT IN ARMENIA AND КАZAKHSTAN (EDUCATION IN THE 21ST CENTURY, 2023)
The comparative analysis of higher education management in different countries has becomeextremely relevant and highly valuable in the world today. These studies address two importantissues: i.e. the exchange of cognitive and advanced experience and definite contribution to thedevelopment of Comparative Pedagogy. Furthermore, the article compares the higher educationmanagement of the two EAEU member states: i.e. Armenia and Кazakhstan as well as presentssimilarities and differences, achievements and problems of the management system. In particular,reforms that are implemented both in Armenia and Кazakhstan in the context of the BolognaProcess are presented in the article. The present article conducts a comparative analysis of ThreeDegree Education System, Management System and Assessment System.
Keywords: Higher Education, Management System, Educational Reforms, Three Degree Education System, Assessment System,.